NOVEL NON-INVASIVE SEVERITY MARKERS IN IDIOPATHIC PULMONARY FIBROSIS - Rodionova, V.V.; Karasova, O.V.; Bekh, O.E.; Tkachenko, V.A.; Gordiienko, Iu.A. (World of Medicine and Biology, 2020)
Idiopathic pulmonary fibrosis is a severe, steadily progressive disease. Lack of specific signs and presence of individual variations in the course of the disease indicate the need to find additional non-invasive markers for diagnosis, estimation of the disease severity and monitoring of treatment effectiveness. Therefore, this study aimed to determine activities of gelatinase A and gelatinase B activities, as well as progelatinase B/lipocalin complex in patients with moderate and severe IPF. It was found that increased gelatinase A and gelatinase B activities correlated with the disease progression. Increased activities of progelatinase B and its active form at different stages of the disease can be used as markers of the severity of the fibrotic process, while gelatinase A activity can indicate its stage. Changes in the progelatinase B/lipocalin complex activity reflect clinical signs and symptoms during the idiopathic pulmonary fibrosis course and are associated with the severity of the disease.